2001
DOI: 10.1183/09031936.01.00203101
|View full text |Cite
|
Sign up to set email alerts
|

The repeatability of nonbronchoscopic bronchoalveolar lavage differential cell counts

Abstract: The repeatability of nonbronchoscopic bronchoalveolar lavage differential cell counts. T.J. Warke, S. Kamath, P.S. Fitch, V. Brown, M.D. Shields, M. Ennis. #ERS Journals Ltd 2001. ABSTRACT: Airway inflammation in children can be assessed by nonbronchoscopic bronchoalveolar lavage (BAL). Little is known about the repeatability of cell counts in the BAL obtained.Children (n=43) attending for elective surgery were studied. Cell counts were obtained following a nonbronchoscopic lavage. Two samples were obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The protected catheter has the advantage of avoiding contamination of the sample with upper airway flora or secretion. (51) Some studies have confirmed the reproducibility of culture results (51) and of differential cell counts (52) in different samples obtained with this technique.…”
Section: Mechanical Ventilation and Non-bronchoscopic Balmentioning
confidence: 69%
“…The protected catheter has the advantage of avoiding contamination of the sample with upper airway flora or secretion. (51) Some studies have confirmed the reproducibility of culture results (51) and of differential cell counts (52) in different samples obtained with this technique.…”
Section: Mechanical Ventilation and Non-bronchoscopic Balmentioning
confidence: 69%
“…Excellent repeatability, as indicated by a Lin's concordance coefficient, Rc, Ͼ0.9 [5] was observed for the major breath metabolites acetone, isoprene and ammonia (Table 1). For all metabolites examined observed mean coefficients of variability (Cv), were Ͻ20%.…”
Section: Experiments Imentioning
confidence: 80%
“…Analysis of repeatability was performed on logtransformed data through computation of Lin's concordance correlation coefficient [5] and the mean intraindividual coefficient of variability, determined as the average ratio of the standard deviation and the mean of paired datasets. Use of log-transformed data is in accordance with previous studies which show the concentrations of common breath metabolites follow more closely a log-normal distribution [6].…”
Section: Breath Sampling Methodologymentioning
confidence: 99%
“…BAL and BAL examination BAL was obtained using a standardised and repeatable [26] nonbronchoscopic technique. Briefly, with the child's head turned to the left, a catheter was passed as far as possible through the endotracheal tube, ensuring that it went beyond the estimated carina site.…”
Section: Methodsmentioning
confidence: 99%